2020
DOI: 10.1016/j.ecolmodel.2020.109224
|View full text |Cite
|
Sign up to set email alerts
|

Dietary bioaccumulation of persistent organic pollutants in the common sole Solea solea in the context of global change. Part 1: Revisiting parameterisation and calibration of a DEB model to consider inter-individual variability in experimental and natural conditions.

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…It has been observed that wildlife including fish can easily bioaccumulate xenobiotics such as PCBs especially when such substances are available in much higher levels in the environment than what is obtainable within the host organism [33]. Dietary bioaccumulation of POPs in the common sole Solea solea from French waters has been reported [34]. From a biochemical point of view, PCBs would be expected to bioaccumulate to varied levels in fish owing to their unique composition and location of chlorine atoms which would invariably exhibit different potential for bioavailability and consequent uptake by fish.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that wildlife including fish can easily bioaccumulate xenobiotics such as PCBs especially when such substances are available in much higher levels in the environment than what is obtainable within the host organism [33]. Dietary bioaccumulation of POPs in the common sole Solea solea from French waters has been reported [34]. From a biochemical point of view, PCBs would be expected to bioaccumulate to varied levels in fish owing to their unique composition and location of chlorine atoms which would invariably exhibit different potential for bioavailability and consequent uptake by fish.…”
Section: Resultsmentioning
confidence: 99%
“…The models share the same assumptions and model setup, but they differ in species-specific parameter values. For parameterization of the S. solea model, we focused on the study by Mounier et al [38] and on the latest available Add-my-pet entry (Teal, AmP Solea solea, version 2015/08/28). Both of these versions of the S. solea models were parameterized using the AmP tool setup [39], so we merged the scripts and complemented the data with data on larval growth and development at several temperatures [40,41].…”
Section: Model Parameterization For S Solea and S Senegalensismentioning
confidence: 99%
“…When sufficient information is available and inter-individual variability is in focus, variability can be integrated into DEB models via one or more physiological parameters (e.g., [59,60]). However, our choice was motivated by the overall aim to focus on the role of the two environmental factors (temperature and food availability) in shaping observable responses in growth and maturation rates while excluding differences resulting from other factors (e.g., as was done in [38,54,55]).…”
Section: Study Design-assumptions and Choicesmentioning
confidence: 99%
“…DEB models can predict biological traits (e.g. food ingestion, growth) of interest in toxicokinetic models, which can be further predicted under dynamic environmental conditions (especially food quality, food availability and temperature) over an animal's life cycle 147 . This can facilitate to some extent the relationship between processes simulated at individual and cohort levels.…”
Section: Process Formulation and Model Selectionmentioning
confidence: 99%